Comparison of spectra and mean glandular dose (MGD) with tube voltage used in digital mammography for simulated, metrological and clinical cases. (October 2021) - Barbosa da Silveira Gatto, Leandro; Braz, Delson; Pacifico, Leonardo; Travassos, Paulo Cesar; Goncalves Magalhaes, Luis Alexandre
Abstract: Mammography has a crucial role in breast cancer detection. The National Cancer Institute (INCA) estimates that 29.7% of the cancer cases in Brazil are related specifically to the breast. It is necessary to evaluate the mean glandular dose with a new solid-state detector in a digital radiography system, utilizing PMMA phantoms and spacers for different thicknesses. The Selenia Dimensions (Hologic, Bedford) direct radiography (DR) system can perform full-field digital mammographies through digital detectors. This system uses new technologies, such as the digital breast tomosynthesis system (DBT), and employs a sequence of projections acquired over the breast, resulting in images with low contrast. The estimation of breast dose is an important part of mammographic quality control for x-ray mammography. Nevertheless, there are currently no standard protocols for the dosimetry of breast imaging in 3D. Additionally, a x-ray spectra function is crucial to measure a considerable output in x-ray spectrometry. The purpose of this work was to assess the mean glandular dose (MGD) and the spectra in slabs of polymethyl methacrylate (PMMA) and breast equivalent thickness through digital mammography using four experiments: a Hologic Selenia Dimensions mammograph with a solid-state detector; a spectrometer (only for the spectra, in this case); a clinical COMET x-ray tube with a solid-state detector; and the MCNPX code. References recommend that the real environments that work well with digital mammography are in the following tube voltages: 25 kVp; 26 kVp; 28 kVp; 31 kVp and 33 kVp. Taking into account several thicknesses of PMMA, the results of both the MGD in metrological, clinical and simulated cases were in accordance with the references, from 30 mm of PMMA. All the spectra for all cases have indicated good agreement with the references. Highlights: X-ray spectra and MGD were measured using different breast thicknesses in a digital mammograph with a solid-state detector. X-ray spectra were obtained through an x-ray spectrometer using several breast thicknesses. X-ray spectra and MGD were measured using different breast thicknesses in a metrological tube with a solid-state detector. An MCNPX simulation, modeling the x-ray tube for mammography and the other accessories, for different breast thicknesses.